Factors Leading to Intra Uterinegrowth Restriction in Termneonates - Muhammad Usman, Kamil Ziad Rajper, Jai Parkash, Ariba Fahim, Saeed Ahmed, Manoj Kumar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The pathologic inhibition of intrauterine fetal growth and in capacity of fetus to develop to its full potential are both considered symptoms of intrauterine growth restriction. Nearly 10% of pregnancies experience impaired fetal growth. Since FGR was discovered to be a cause of neonatal death, approximately 50% of still births have been determined to be FGR, leading to a drop in unexplained still birth from 67–70% to 15%. A retrospective diagnosis of IUGR is made after the fact in roughly 75% of instances, compared to a detection rate of 15% in low-risk pregnancies. Objective: To assess the factors leading to Intra Uterine Growth Restriction among term neonates presenting to a National Institute of child health Karachi. Materials and Methods : A descriptive Cross-Sectional study was conducted at Department of Paediatrics of National Institute of child health Karachi from August2019 to February2020. Using a consecutive sampling method, 116 mothers were included in the study. Data was analyzed using SPSS version 23. Results: Mean age of the patient was 25.15 ±3.49 years. Mean weight, height, and BMI of the patients was 60.17±5.12kg,1.54±0.06 cm and 27.19 ±5.08kg/m2 respectively. Nulli parity was the most highest factor observed in 73 (63%) of the patients followed by low maternal BMI 64(55%), anemia 48(41%) and preeclampsia 37(32%). Conclusion: The finding of the study showed frequency of nulliparity was the found to be higher leading factor for IUGR followed by low maternal BMI, anemia, and preeclampsia among term neonates presenting to a tertiary care hospital. Keywords: Intra Uterine Growth Restriction, preeclampsia, low maternal BMI, anemia, nulliparity